Self-governance in the Guides of Suicide Prevention and Postvention (Andamios, Revista de Investigación Social, 2025)
The problem of suicide is usually confronted by the implementation of measures aimed at reducing attempts and deaths through prevention, intervention, and postvention. However, there is a tendency to overlook the fact that the application of these measures relies on strategies of the governance of subjectivity that belong to the hegemony of clinical practice and mainstream psy disciplines. Accordingly, this research analyses four guides in Spanish, three international and one national (Spain), that set a series of practices and technologies of the self that tend to place the responsibility of (self)containment on the mainly affected by suicide: survivors. Therefore, this text presents a recently developed perspective that problematizes the governance of suicide and its therapeutical logics.
Keywords: Governmentality; postvention; prevention; suicide; therapy